2018
DOI: 10.1007/s11906-018-0877-8
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Metabolic Phenotyping in Blood Pressure Research

Abstract: Purpose of the ReviewThis review presents the analytical techniques, processing and analytical steps used in metabolomics phenotyping studies, as well as the main results from epidemiological studies on the associations between metabolites and high blood pressure.Recent FindingsA variety of metabolomic approaches have been applied to a range of epidemiological studies to uncover the pathophysiology of high blood pressure. Several pathways have been suggested in relation to blood pressure including the possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 78 publications
(55 reference statements)
2
24
0
Order By: Relevance
“…Several metabolomic studies have demonstrated the existence of biological signatures in the blood and urine of patients with high blood pressure from various regions, including African populations, and using various analytical platforms and study designs. These studies have been recently reviewed 9,10 . The metabolomic signatures published to date showed a wide variety of quantitative metabolite traits related to arterial hypertension such as amino acids (alanine, serine, glycine, methionine, arginine, tyrosine and isoleucine), nucleotide bases (adenine and uracil), hormones (epiandrosterone sulfate, 5 α-androstan-3β-diol disulfate, androsterone sulfate, melatonin, cortolone, dihydroxyphenylglycol, and hydroxyandrosterone), organic acids (hippurate, pyruvate, hexadecanedioate, formate, methyl nicotinate, dicarboxylic acids, butyrate and fumarate, lactate, malate and pyruvate), and hexoses [11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%
“…Several metabolomic studies have demonstrated the existence of biological signatures in the blood and urine of patients with high blood pressure from various regions, including African populations, and using various analytical platforms and study designs. These studies have been recently reviewed 9,10 . The metabolomic signatures published to date showed a wide variety of quantitative metabolite traits related to arterial hypertension such as amino acids (alanine, serine, glycine, methionine, arginine, tyrosine and isoleucine), nucleotide bases (adenine and uracil), hormones (epiandrosterone sulfate, 5 α-androstan-3β-diol disulfate, androsterone sulfate, melatonin, cortolone, dihydroxyphenylglycol, and hydroxyandrosterone), organic acids (hippurate, pyruvate, hexadecanedioate, formate, methyl nicotinate, dicarboxylic acids, butyrate and fumarate, lactate, malate and pyruvate), and hexoses [11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%
“…In this study, we investigated associations of a large number of circulating metabolites with longitudinal BP progression in a population-based cohort. Accounting for multiple testing, and in mixed models with multivariable adjustment, baseline levels of 4 metabolites (ceramide [d18:1, C24:0], triacylglycerol [C16:0, C16:1], total glycerolipids, and oleic acid [C18:cis [9]1]) were positively associated with longitudinal change in DBP. One metabolite (cholesterylester C16:0) was negatively associated with DBP change.…”
Section: Discussion Principal Observationsmentioning
confidence: 99%
“…In the validation phase, 11 metabolites available in the validation cohort that had similar structure to the 5 top findings in the discovery cohort were investigated. Diacylglycerol ( In secondary analyses in the discovery cohort, cubic spline models demonstrated chiefly linear association of metabolites on diastolic BP among ceramide (d18:1, C24:0), triacylglycerol (C16:0, C16:1), glycerolipids, and cholesterylester (C16:0), except oleic acid (C18:cis [9]1; Figure III in the Data Supplement). In sensitivity analyses, the heterogeneity between participants with or without antihypertensive treatment during follow-up was low (I square=0, Figure IX in the Data Supplement).…”
Section: Associations Of Baseline Metabolites With Longitudinal Bp Chmentioning
confidence: 97%
See 1 more Smart Citation
“…Metabolomics is a high-throughput mass spectrometry method that offers a powerful platform tools to explore metabolic alterations associated with pathophysiological states. Several studies have indeed proven that metabolomics provide important insight into cardiovascular disease pathogenesis such as cardiac hypertrophy, heart failure, coronary heart disease, cardiometabolic disease, and hypertension as well as identify new potential cardiovascular disease biomarkers (Nikolic et al, 2014;Tzoulaki et al, 2018). Metabolomic profiling is also thought to integrate valuable information reflecting genomic, epigenetic, and transcriptomic variation with the effect of environmental exposures such as diet, physical activity which is unique for each individual (McGarrah et al, 2018;Leon-Mimila et al, 2019).…”
Section: Introductionmentioning
confidence: 99%